Physical Characterization of Chitosan-based Syzygium polyanthum Leaves Extract Nanoparticles - Hidayati, Evi Nurul; Rahayyu, Annisa Maulidia; Azzahra, Fauzia (Universitas Muhammadiyah Surakarta, 2023)
Indonesia is one of the most abundant in natural resources countries in the world. The bay leaves are well- known among the locals and have various pharmacological properties, including anti dyslipidemia. Currently, the use of nanoparticle technologies in dyslipidemia treatment is quite popular. These treatments have numerous advantages such as enhancing the potency of dyslipidemia agents. The purpose of this study is to develop chitosan-based nanoparticles made from Syzygium polyanthum leaves extract using crosslink method. Chitosan is used as the polymer and STPP as the crosslinker with the ratio of chitosan:STPP is 5:1. Two formula is generated, F1 is chitosan-based nanoparticle extract and F2 is chitosan-base nanoparticle blank. Syzygium polyanthum extract contains alkaloid, flavonoid, saponin, quinone, and tannin, as determined by secondary metabolites screening. The total flavonoid content of Syzygium polyanthum leaves extract determined as quercetin is 0.04%. Physical properties of generated nanoparticles such as size, polydispersity index (PI) and zeta potential are investigated. Particle sizes of nanoparticles F1 and F2 are 180.1 ± 0.5 nm and 464.3 ± 25.98 nm with the PI values of F1 and F2 are 0.220 ± 0.02 and 0.563 ± 0.112 respectively. Zeta potential value for F1 is 21.8 ± 1.74 mV and F2 is 17.8 ± 0.21 mV. The entrapment efficiency is evaluated to determine the extract content of the nanoparticle, and the result is 47.13%. From this research, the chitosan-based nanoparticles containing Syzygium polyanthum formula have good physical properties. Further investigation is needed to evaluate its potential as anti-dyslipidemia.